Uptake of COVID-19 vaccine among female healthcare workers in Syria: results from a 2022 cross-sectional survey - Zlatko Nikoloski; Elnur Aliyev; Robert Bain; Leonardo Menchini; Sahar Hegazi; Mai Zalkha; Shaza Mouawad; Neha Kapil; Amaya Gillespie (Conflict and Health)
Abstract Background Healthcare workers play an important role in administering COVID-19 vaccines, particularly in conflict-affected settings. Syria has endured a protracted conflict for over a decade and while most of the healthcare workers in the country have been vaccinated with at least one COVID-19 vaccine dose, vaccinating all of them would reduce their risk of COVID-19 complications, given their daily interactions with patients. Methods The goal of this study was to better understand the main barriers to uptake of COVID-19 vaccines among female healthcare workers in Syria. Using data from a wider national survey of 17,000 respondents conducted between October and November 2022, we analysed a sub-sample of 4136 responses from female healthcare workers, across 14 Governorates. The main outcome of interest was vaccination status, (vaccinated, willing (but not yet vaccinated), unsure about vaccination and finally, those unwilling to receive a COVID-19 vaccine). We present descriptive information about the sample and conduct a multivariate logistic regression analysis to shed light on some of the barriers preventing COVID-19 vaccination uptake. Results We find that the vast majority (93.7%) of female healthcare workers have received at least one COVID-19 vaccination dose. We find that attitudes and beliefs around COVID-19 vaccines impact upon the decision to get a vaccination—positive attitudes around effectiveness and safety of the vaccines increase the likelihood of being vaccinated or willing to be vaccinated. More specifically, healthcare workers which believe in the safety of the vaccines are twice as likely to get vaccinated relative to those who don’t. By contrast, we find that neutral attitudes regarding the vaccines are associated with vaccine indecision among female healthcare workers. In addition, we also find that female healthcare workers tend to trust COVID-19 vaccine information from their peers—close to 99% of vaccinated female healthcare workers tend to trust the vaccine information received from their peers. Implications While the vaccination rates among healthcare workers are high, the results could further help in devising strategies for tackling the structural and individual barriers towards vaccine uptake among healthcare workers.